Necesidad de reformar el artículo 47 de la ley de servicio publico con la finalidad de evitar que se vulnere el derecho al trabajo establecido y garantizado en la constitución de la República Del Ecuador - Maza Gonzaga, Jose Miguel (2015)
One of the most alarming and chaotic situations being experienced by our country, and specifically the public sector is being subjected to the so-called “mandatory waiver”, which is framed in Presidential Dece 813, a disguised name illegal and unfair dismissal inmoral, in full view of the present Constitution, where paradoxically protect and guarantee the rights of workers, who are internationally recognized too much. This is the reality of hundreds of Ecuadorians who work in public service, which is inminent tramples human rights of the people, and without scruples are removed from their jobs, without detriment to examine the economic situation of the Servers and the serious repercussions for his family, with the faint hope that the so-called “compensation” severely affected its economy recover. For this situation, which has ben conducted in this paper thorough research regarding this legal concept, which was introduced in Ecuador in mid- November of 2011, which brought serious repercussions for the thousands of public servants they were suddenly fired from their jobs without explanation, were prevented only with the police force even enter the workplace, which for many years was personal and family support, and without explanation, and after a full assessment is questionable the indemnified the first to leave immediately and no other time to receive the long-awaited compensation allowing them to recover something at least its devastated economy. The incumbent government always tried to justify the fact raised, however never know for sure what it was the same reason to dump thousands of people form their jobs within the public service.